Island Placenaming and Insular Toponymies. (September 2015) - Nash, Joshua
Abstract : Islands as distinct research sites have been given little specific attention by toponymists. The physical segregation, distinctness, and isolation of islands from continental environments may provide linguists and onomasticians with significant micro case studies for examining the role of toponyms as proper names. This article outlines the possibility of how the cultural and ecological nature of the toponymy of (small) island situations contributes to a place's onomasticon. It is claimed the principal difference which distinguishes island people from non-island people is island people's self-perceived difference. It is speculated this difference and awareness can be observed and demonstrated in island toponymies, both through distinction based on belonging to an island-specific language group and through knowledge and use of locally peculiar eponymous toponyms. The argument concludes by suggesting that a description of a place and culture based in the self-perceived awareness of the holders of island placenaming history and knowledge — an island's toponymic ethnography — is an apt descriptor for future work into islotoponomastics.